The research of the efficiency of the performance of a male national picked team of Ukraine on the world championship on basketball in 2014 - Irina Pomeschikova; Nataliya Pashchenko; Nataliya Chycha; Yevgeniya Strelnykova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the efficiency of game indicators of a male national picked team of Ukraine on the World Championship on basketball in 2014. Material and Methods: theoretical analysis of scientifically methodical literature, pedagogical observations, methods of mathematical statistics. Results: indicators of the efficiency of a game activity of basketball players in games of the World Championship of 2014 were studied. Game indicators of the Ukrainian team are analysed, the efficiency of individual actions of the leading basketball players of the world is considered. Conclusions: it is established that basketball players of Ukraine had a result below an average on all components of indicators of technical and tactical actions in attack and defense in games of the World Championship in 2014, except the efficiency of free throws where the accuracy of their performance was the highest in the group. It is revealed that the defender Eugene Jeter was the leader of the Ukrainian team in this championship.